LITERATURE REVIEW DETERMINATION OF PLANNING AND ORGANIZATION IN EDUCATIONAL INSTITUTIONS: ANALYSIS OF LEADERSHIP AND ORGANIZATIONAL CULTURE - Fitriyani, Fitriyani; Kemas Imron Rosadi; Alfian, Muhammad (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews Determination Planning and Organizing: Leadership and Culture Analysis Organization, A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) Leadership influences planning; 2) Culture Organization influences planning; 3) Leadership has an effect on Organizing; 4) Culture Organization influence on Organizing; and 5) Planning has an effect on Organizing.